1998
DOI: 10.1016/s0006-3495(98)77967-6
|View full text |Cite
|
Sign up to set email alerts
|

Energy Transfer and Charge Separation in Photosystem I: P700 Oxidation Upon Selective Excitation of the Long-Wavelength Antenna Chlorophylls of Synechococcus elongatus

Abstract: Photosystem I of the cyanobacterium Synechococcus elongatus contains two spectral pools of chlorophylls called C-708 and C-719 that absorb at longer wavelengths than the primary electron donor P700. We investigated the relative quantum yields of photochemical charge separation and fluorescence as a function of excitation wavelength and temperature in trimeric and monomeric photosystem I complexes of this cyanobacterium. The monomeric complexes are characterized by a reduced content of the C-719 spectral form. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

18
201
0

Year Published

2003
2003
2014
2014

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 173 publications
(219 citation statements)
references
References 47 publications
18
201
0
Order By: Relevance
“…All data points were taken using the same power of the excitation laser flashes (20 mJ) at different wavelengths. This result extends the action spectrum for PS I almost 80 nm further out into the red if compared with previous reports (53). It is noteworthy that P 700 was oxidized in almost 70% of the centers when using excitation light at 780 nm where 532 99 100 730 87 39 780 65 2 820 20 0…”
Section: Quantification Of the Far-red Light-induced Radical Signals-supporting
confidence: 80%
See 2 more Smart Citations
“…All data points were taken using the same power of the excitation laser flashes (20 mJ) at different wavelengths. This result extends the action spectrum for PS I almost 80 nm further out into the red if compared with previous reports (53). It is noteworthy that P 700 was oxidized in almost 70% of the centers when using excitation light at 780 nm where 532 99 100 730 87 39 780 65 2 820 20 0…”
Section: Quantification Of the Far-red Light-induced Radical Signals-supporting
confidence: 80%
“…This shows that charge separation can be driven with light 140 nm above the absorption peak at 700 nm for P 700 and more than 100 nm above the absorption band of the so-called red Chls (see below) (31). Our results also extend the action spectrum of PS I 80 nm further out to the red than reported previously (53).…”
Section: Simultaneous Detection Of Ps I and Ps Ii Photochemistrysupporting
confidence: 79%
See 1 more Smart Citation
“…For example, although the flash-induced (P700 ϩ⅐ -P700) absorbance difference spectra of T. elongatus and Spinacia oleracea (spinach) are rather similar (15,16), those recorded for Anabaena variabilis (15) and C. reinhardtii (17, 18) look different.…”
Section: Photosystem I (Ps I)mentioning
confidence: 96%
“…They were modelled as β-carotene (Jordan et al 2001) which has been previously shown as the dominant carotenoid in PSI (Palsson et al 1998). Seventeen carotenoid molecules showed the all-trans configuration, 2 are 9-cis, and 3 contain one of 9, 9'-cis 9, 13'-cis and 13-cis bonds.…”
Section: Localization Of β-Carotene Molecules In Photosystem Imentioning
confidence: 99%